The Effect Of Environmental, Social and Governance (ESG) Disclosure on Firm Performance: The Role of Ceo Tenure - Triyani, Agus; Setyahuni, Suhita Whini; Kiryanto, Kiryanto (Universitas Muhammadiyah Malang)
This paper aims to investigate the effect of environmental, social, and governance (ESG) disclosure on firm performance, which is measured by ROE. We also analyze the role of CEO tenure on the relationship between ESG disclosure and ROE. We used 159 samples of public listed companies in Indonesia during period of 2012 to 2016. We employed multiple regression technique to assess the research model. The findings show that ESG disclosure has a positive impact on ROE. The better the quality of ESG disclosure can enhance the level of ROE. In addition, we found a moderating effect of CEO tenure on the relationship between ESG disclosure and ROE. However, CEO tenure plays a role in decreasing the relationship between ESG disclosure and ROE. Our empirical evidence support the process of sustainability investment by using ESG data analysis, to get more comprehensive picture regarding companies sustainability performance. The findings of this study are expected to provide strong evidence regarding the importance of ESG disclosure in enhancing corporate performance. Furthermore, the findings are also expected to be able to ensure potential investors in using ESG disclosure to evaluate corporate sustainability performance.